NILAI-NILAI DAN MAKNA SIMBOLIK TRADISI NGANGGUNG - Waluyo, Muhammad Edy (Sabda: Jurnal Kajian Kebudayaan, 2015)
The tradition of Nganggung in Petaling Bangka, Province of Bangka Belitung Islands is a tradition that has been rooted in its community. This study reveals about values and symbolic meanings of the Nganggung tradition in the village of Petaling in which in the tradition have these values of 1) spiritual, 2) economical, 3) mutual cooperation and togetherness and 4) political. This tradition also has a symbolic meaning, we can see it at Nganggung attributes such as tudung saji that represents the preservation of the indigenous plants of pandanus forest, as well as means of preserving of lofty values of its ancestors; from its shape, tudung saji resembles a parabole that represents the tradition of Nganggung as a shelter for all; red, as a dominant color of tudung saji symbolizes courage and high work ethic; cord symbolizes the fastener with a diversity of community and a sense of belonging; while talam, a round pan, shape symbolizes the dynamic attitude and flexibility of its inhabitants.